Perancangan Sistem Informasi Penjualan Perangkat Seluler berbasis Web menggunakan Framework Laravel di Mobile Cell Toraja - Santoso, Wahyu Aji; Susetyo, Yeremia Alfa (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In order to face increasing competition and improve operational efficiency, Mobile Cell plans to use the Laravel Framework as the development framework. The purpose of this research is to provide technological solutions to enhance operational efficiency and improve customer experience. The implementation of the system involves the creation of Use case Diagram, Activity Diagram, and system page views. Laravel applies the MVC (Model-View-Controller) architecture pattern, which simplifies the development and maintenance of applications. The Testing of the system shows success in key functions such as registration, login, adding to the shopping cart, checkout, payment, and viewing order history. This can be inferred from the 100% validity of the test results for each function.